Preserving tacit knowledge into public organizations (Advances in Knowledge Representation, 2022)
Knowledge Management (KM) has been used by the organizations as a tool to organize the knowledge produced by social actors in order to preserve organizational knowledge. However, KM methodologies, usually supported by technologies, do not help organizations on how to treat tacit knowledge in a systematic way. The goal of this research is how to identify and preserve tacit knowledge of experienced employees in order to create and maintain organizational knowledge. A case study was undertaken within a public research and teaching organization, in Brazil. By using the fundamentals of Grounded Theory, activity analysis and self-confrontation techniques, it was analyzed the task of calculation of quarterly GDP trying to identify involved activity’s tacit abilities. The results show that it is possible to bring to the conscious of practitioner his tacit abilities and judgments. These are then used as the basis for a more effective training of novices, reducing the time of apprenticeship in a specific activity that need to be preserved.